On versus off-hour care of patients with acute coronary syndrome and persistent ST-segment elevation in certified German chest pain units - Breuckmann, Frank; Giannitsis, Evangelos (European heart journal - acute cardiovascular care, 2017)
Background:Regional healthcare projects improve the off-hour care of patients with acute coronary syndromes and persistent ST-segment elevation myocardial infarction (STEMI). To analyse differences in quality of care between on and off-hour care of STEMI patients admitted to certified German chest pain units.Methods:A total of 1107 STEMI patients from the German chest pain unit registry were enrolled. Analyses comprised critical time intervals (symptoms to first medical contact (FMC), FMC to admission, symptoms to admission, symptoms to balloon, FMC to balloon, door to balloon times) and major adverse cardiac and cerebrovascular events at follow-up.Results:54.8% of patients were admitted off-hours. Symptoms to admission (2:28 (1:28?5:20 h) vs. 3:16 h (1:35?8:06 h), P<0.001), symptoms to FMC (1:15 h (0:33?3:00 h) vs. 2:00 h (0:40?6:46 h), P<0.001) and FMC to admission intervals (0:45 h (0:30?1:20 h) vs. 0:52 h (0:32?1:35 h), P=0.09) were shorter during off-hours. Percutaneous revascularisation rates were high and without difference between on and off-hours (95.5% vs. 96.8%, P=0.30). Door to balloon times were significantly less during on-hours (0:32 h (0:18?1:06 h) vs. 0:44 h (0:23?1:20 h), P<0.01) without negative impact on the proportion of patients with a door to balloon time of <60 min (72.6% vs. 68.4%, P=0.19), symptoms to balloon (3:49 h (2:12?10:46 h) vs. 3:30 h (2:04?7:41 h), P=0.08) or FMC to balloon times (1:26 h (0:56?2:22 h) vs. 1:30 h (1:03?2:29 h), P=0.14). Major adverse cardiac and cerebrovascular event rates did not differ significantly between on and off-hours (log-rank test P=0.36).Conclusions:The German chest pain unit network ensures rapid and structured preclinical and in-hospital care independent from the circadian variation of admission. Slower door to balloon times off-hours are compensated by faster symptoms to admission or symptoms to FMC intervals. Further efforts should focus on patient awareness programmes on-hours and STEMI alarming tracks off-hours.
First published: December 29, 2015
Gesehen am 10.07.2018